Experimental investigations of Soyabean and Rapeseed SVO and biodiesels on engine noise, vibrations, and engine characteristics. (15th February 2019) - Patel, Chetankumar; Tiwari, Nachiketa; Agarwal, Avinash Kumar
Highlights: Effects of biofuels on combustion, noise and vibrations were investigated. Lower peak cylinder pressure, HRRmax & longer combustion duration for biofuels. Lower combustion noise and vibrations from biofuels. Noise and vibrations were closely coupled. Biodiesels showed higher CO, and lower BTE, HC & NOx emissions. Abstract: Genset engines are popular for power backup as well as for agricultural applications in rural areas. However these engines are noisy and emit toxic pollutants. It is therefore important to develop noise reduction methodologies for genset engines since noise regulations are becoming increasingly stringent globally. Experimental investigations were carried out on a single cylinder engine to assess combustion, noise and vibration characteristics using Soyabean and Rapeseed biofuels (straight vegetable oil (SVO) and Biodiesel). In addition, performance and emission characteristics of these fuels were also investigated. Through this study, it has been found that there is a strong correlation between the heat release rate (HRR) and combustion noise as well as external noise. Higher was the HRR, higher were the magnitudes of combustion noise and external noise. Similar correlation also existed for vibrations.